UIGM Student Satisfaction Level with E-Learning Using End User Computing Satisfaction (Eucs) - Amar Sahona; M. Amaruna Sahona; Terttiaavin's M.Com; Gergely Maja (Yayasan Adra Karima Hubbi, 2023)
The Ministry of Education and Culture responded by issuing a policy of learningfrom home, through online learning, the current education system must be ready tomake the leap to transform online learning for all students. E-learning is a distancelearning process whose implementation is supported by computers and internettechnology, so that the learning process can be carried out at any time without ameeting between lecturers and students. From the explanation above, a study wasconducted that measured the Level of Satisfaction of E-learning Students at Indo GlobalMandiri University using the End User Computing Sastification (EUCS) method. Thisresearch will analyze the level of student satisfaction using the E-learning web whichhas an important role in higher education. Analysis of the level of satisfaction usingEUCS is expected to be a measuring tool for the success of a system The model of EndUser Computing Satisfication (EUSC) was developed by Doll & Torkzadeh. EUCS is amethod that can be used to measure the level of satisfaction of users of a system, bycomparing expectations and reality of a system. Evaluation using the EUCS model ismore focused on end user satisfaction with technological aspects. The dimensions inEnd User Computing Satisfaction (EUCS) according to Doll & Torkzadeh are five, namelycontent (Content), accuracy (Accuracy), form (Format).From the results of dataprocessing that has been done previously, it can be concluded in this study that theresults of quantitative analysis on the variable respondents who strongly agree (SS) are80.0%, who agree 20.0% so it can be concluded that user satisfaction with theperformance of e-learning students of Indo Global Mandiri University, Faculty ofInformatics Engineering is very satisfied.